Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/nu10122009
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Endothelial Dysfunction Markers in Obese Mexican Children and Adolescents

Abstract: Obesity is a metabolic disease characterized by low-grade inflammation and accompanied by dyslipidemia and up-regulation of other bioactive molecules, creating a predisposition to endothelial dysfunction and metabolic syndrome. We studied the association between gut microbiota diversity and endothelial dysfunction (EDF) markers in obese Mexican children and adolescents. We examined clinical data including metabolic factors and EDF markers in blood samples. Gut bacterial diversity was characterized by high-thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
79
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 54 publications
10
79
2
Order By: Relevance
“…The Principal Coordinate Analysis (PCoA) of inter-individual variation, based on Bray-Curtis distances between the genus-level microbial profiles, nevertheless showed a significant separation between the study groups (p = 1 × 10 −5 , permutation test with pseudo-F ratios) ( Figure 1B). In line with the available literature on the gut microbiota in obesity and metabolic disorders in general [36][37][38][39][40][41], EO patients showed increased relative abundance of Coriobacteriaceae, especially Collinsella, and Streptococcus, as well as reduced proportions of a number of SCFA producers belonging to the Lachnospiraceae and Ruminococcaceae families, including the understudied Oscillospira (p ≤ 0.05, Wilcoxon test). In addition, significantly lower amounts of Parabacteroides, a bacterial genus to which anti-obesogenic effects have recently been attributed [42], were found in EO vs. EC subjects (p ≤ 0.004) ( Figure 2).…”
Section: Gut Microbiota Layout In Elderly Obese Womensupporting
confidence: 78%
See 1 more Smart Citation
“…The Principal Coordinate Analysis (PCoA) of inter-individual variation, based on Bray-Curtis distances between the genus-level microbial profiles, nevertheless showed a significant separation between the study groups (p = 1 × 10 −5 , permutation test with pseudo-F ratios) ( Figure 1B). In line with the available literature on the gut microbiota in obesity and metabolic disorders in general [36][37][38][39][40][41], EO patients showed increased relative abundance of Coriobacteriaceae, especially Collinsella, and Streptococcus, as well as reduced proportions of a number of SCFA producers belonging to the Lachnospiraceae and Ruminococcaceae families, including the understudied Oscillospira (p ≤ 0.05, Wilcoxon test). In addition, significantly lower amounts of Parabacteroides, a bacterial genus to which anti-obesogenic effects have recently been attributed [42], were found in EO vs. EC subjects (p ≤ 0.004) ( Figure 2).…”
Section: Gut Microbiota Layout In Elderly Obese Womensupporting
confidence: 78%
“…The Mediterranean diet is indeed considered the optimal strategy to prevent microbiota dysbiosis and protect intestinal permeability [55]. In line with the literature available on gut microbiota and metabolic disorders [36][37][38][39][40][41], the intestinal microbiota of EO subjects, as compared to non-obese elders (EC) living in the same territory (i.e., Italy), showed several dysbiotic features, including: (i) a tendency to reduced biodiversity (generally recognized as a hallmark of a healthy gut); (ii) decreased relative abundance of health-promoting, SCFA producers (mainly belonging to the Lachnospiraceae and Ruminococcaceae families, i.e., Lachnospira, Blautia, Coprococcus, Roseburia, Ruminococcus and Oscillospira) as well as Parabacteroides; and (iii) increased proportions of subdominant taxa, such as Collinsella and Streptococcus. While SCFAs are well known to have a key, multifactorial role in the host physiology, being fundamental for the maintenance of metabolic and immunological homeostasis [56], Collinsella and Streptococcus have been hypothesized to be involved in a variety of inflammation-based disorders [39,[57][58][59][60].…”
Section: Discussionmentioning
confidence: 63%
“…Human gut microbiota derives energy from dietary fiber through fermentation and produces short-chain fatty acids (SCFAs) to influence host lipid energy metabolism [80]. Diet plays a significant role in modulating microbial diversity and reports have indicated that a high-fat diet is associated with obesity, whereas a fiber-rich diet has the potential for reducing the risk of obesity [81,82]. Gut microbiota play a critical role in hemostasis for maintaining human health, with gut dysbiosis contributing to the development and progression of various diseases including CVD, obesity, T2DM, NAFLD, and even some types of cancer [83].…”
Section: Impact Of Human Gut Microbiota On Vascular Endothelimmentioning
confidence: 99%
“…Earlier studies have reported the relationship between the brain and the GI system, the so-called gut-brain axis or brain-gut axis. It has been hypothesized that GI dysfunctions could reflect the disruptions of the microbiome-gut-brain axis, leading to serious GI inflammatory diseases (e.g., acute pancreatitis or inflammatory bowel disease), endothelial dysfunction, altered immune functioning and regulation of appetite control, neural inflammation, subsequent neurodegeneration, cognitive or psychoneurological disorders (e.g., depression, anxiety, autism, dementia), and disease progression of PD [8][9][10][11][12][13][14][15][16][17][18][19]. In addition to the use of peptides for the improvement of gastrointestinal or digestive dysfunctions [13,[20][21][22], and in order to improve GI function and the balance of microbiota, probiotics could be one of the powerful tools to be used for altering the PD-associated microbiota composition and mitigating the related inflammatory process [12,23].…”
Section: Introductionmentioning
confidence: 99%